Synthesis And Characterization Of CuS By Laser-Assisted Spray Pyrolysis Deposition For pH Sensor Application - Alzuhayre, Fayroz Arif Sabah (2017)
This study involves the novel application of copper sulphide (CuS) films as pH sensors. The synthesized CuS thin films were used as extended gate field effect transistor (EGFET), which was then applied as a pH sensor. The pH sensitivity, hysteresis, repeatability, stability and reliability of the CuS thin films were measured. The effects of thin film material, temperature, illumination, pH sensor thickness, sensor conductivity, sensor surface structure, precursor solvent type on crystal orientation and Metal oxide semiconductor field effect transistor (MOSFET) were studied. The CuS thin films were synthesized on several substrates using spray pyrolysis and laser-assisted spray deposition at substrate temperature of 200°C.